1976
DOI: 10.1161/01.res.38.2.60
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of myocardial blood flow in the exercising dog with restricted coronary artery inflow.

Abstract: SUMMARY The effect of a proximal coronary artery stenosis on transmural myocardial blood flow during exercise was studied in nine dogs with electromagnetic flowmeter probes and hydraulic occluders on the left circumflex coronary artery. Regional myocardial blood flow at rest and during treadmill exercise was estimated with radioactive microspheres 7-10 j»m in diameter. Exercise studies were performed during unrestricted coronary artery inflow (control exercise) and during partial inflation of the occluder to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(35 citation statements)
references
References 31 publications
6
29
0
Order By: Relevance
“…This is consistent with previous observations using hydraulic occluders to create coronary artery stenoses (6,10) or ameroid constrictors to create coronary occlusions (1 1-15). The mechanisms by which flow decreases to subendocardial layers include an increase in the fraction of total flow which occurs during systole (16), intense vasodilation ofcoronary resistance vessels, and reductions in distal coronary artery perfusion pressure (17).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous observations using hydraulic occluders to create coronary artery stenoses (6,10) or ameroid constrictors to create coronary occlusions (1 1-15). The mechanisms by which flow decreases to subendocardial layers include an increase in the fraction of total flow which occurs during systole (16), intense vasodilation ofcoronary resistance vessels, and reductions in distal coronary artery perfusion pressure (17).…”
Section: Discussionsupporting
confidence: 93%
“…Although it has been previously shown that regional dysfunction may occur after exercise in the presence of coronary artery stenosis (5), the mechanisms underlying post-exercise dysfunction have received little attention. In the presence of a flow-limiting coronary artery stenosis, exercise results in an alteration of the transmural dis-tribution of myocardial perfusion such that flow is distributed preferentially to the subepicardium, while the subendocardium is most severely hypoperfused (6). Since distal coronary vasodilation and tachycardia may persist for some time after the cessation of exercise, it is possible that persistent subendocardial hypoperfusion would continue during the early post-exercise period.…”
Section: Introductionmentioning
confidence: 99%
“…The redistribution ofregional myocardial blood flow in the partially occluded region in this study is comparable to that which our laboratory described earlier in animals with partial coronary artery stenosis and ischemia-induced vasodilation (14) and in exercising animals with partial occlusion (13 (26). Earlier studies in our laboratory have shown that the initial localization ofthallium-20 1 is closely related to myocardial blood flow during a wide range of blood flows produced by ischemia and exercise stress (12), and by acute ischemia and recent myocardial infarction (27).…”
Section: Discussionsupporting
confidence: 90%
“…First, intravenous dipyridamole infusion in dosages that cause marked coronary vasodilation effects a distribution of regional myocardial blood flow that is comparable to, as previously reported by our laboratory, blood flow distribution during exercise and partial and complete coronary occlusion (12,13) and during partial occlusion and ischemicinduced vasodilation (14). Second, regression analysis demonstrated that the relationship between the distribution of thallium-201 and myocardial blood flow during dipyridamole infusion was similar to that observed in animals subjected to treadmill exercise.…”
Section: Discussionsupporting
confidence: 77%
“…It seems likely that this regional ischemia resulted from increased myocardial metabolic demands in the face of limited coronary reserve as well as from coronary blood flow redistribution away from the subendocardium during exercise under conditions of partial coronary artery constriction. 9 The severity of the exercise in the present experiments undoubtedly explains the rapidity with which regional dysfunction developed and could account for the occurrence of sudden death in two dogs. The latter event is most unusual during exercise testing in patients.…”
Section: Figure 3 Left Panel: Serial Changes In the Control Segments mentioning
confidence: 62%